Investigating the Impact of Hedge Funds on an Optimally Balanced Portfolio - Kungwane, Keabetswe (University of the Witwatersrand, Johannesburg, 2025)
This study explores the incorporation of hedge funds into balanced investment portfolios, emphasising their ability to enhance returns and mitigate risk through diversification. Analysing monthly return data between January 2007 to December 2023 and sub-period analysis from January 2010 to December 2019, the research evaluates the performance of several hedge fund strategies - Fixed Income, Equity Long/Short, Market Neutral and Multi- Strategy against a synthetic traditional “balanced fund” and the industry balanced fund from Allan Gray. By employing mean-variance optimization methods, the paper seeks to identify optimal asset allocation strategies that maximize returns while minimising risk exposure. In line with regulation 28 of the Pension Funds Act, the results indicate that a 10% allocation to hedge funds in traditional diversified portfolios can substantially improve performance measures adjusted for risk, such as the Sharpe ratio and Jensen's alpha. This research adds to the current knowledge base by demonstrating practical evidence and confirmation of the effectiveness of hedge funds. It provides valuable insights for portfolio management and diversification within the South African financial context. Ultimately, the findings highlight the critical role of alternative asset classes in achieving superior investment performance and volatility reduction.
A research report submitted in fulfillment of the requirements for the Master of Management in the field of Digital Business, in the Faculty of Commerce Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Balanced Fund; Hedge Funds; Multi Strategy; SDG-9: Industry, innovation and infrastructure